Kolaborasi Pola Asuh Orang Tua dan Guru Dalam Mendidik Anak Dengan Metode Agama - Suleman, Vera Febriyanti; Tine, Nurhayati; Ardini, Pupung Puspa (PEDAGOGIKA, 2024)
The pupose of this study is to examine the collaboration between parenting styles of parents and teachers in education children using religious methods at TK Al-Khairaat kindergarten, dembe II, Gorontalo city. This study employed a decriptive qualitative method, focusing on the collaboration between parents and teachers in educating children through religious approaches. The subject involved 6 parents, and 3 teachers. The methods comprised observation, interview, and documentation. The study results showed that there is a parenting style where parents scrictly control the child, the child musr follow all parental commands, and children who do not obey their parents are subject to punishment. There is also a parenting style where parents provide freedom for children to socialize and engage in activities while mainting control over their activities, attending to the child’s needs, and fostering a good relathionship with the child. As for the teachers’s parenting style, they consistenly provide rewards, build good relationship with the children, and teach and instill, values related to ethics, morality, and worship.